2017
DOI: 10.1016/j.yexmp.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor deficit induces activation of renin angiotensin system via SIRT1 modulation in podocytes

Abstract: Vitamin D receptor (VDR) deficient status has been shown to be associated with the activation of renin angiotensin system (RAS). We hypothesized that lack of VDR would enhance p53 expression in podocytes through down regulation of SIRT1; the former would enhance the transcription of angiotensinogen (Agt) and angiotensinogen II type 1 receptor (AT1R) leading to the activation of RAS. Renal tissues of VDR mutant (M) mice displayed increased expression of p53, Agt, renin, and AT1R. In vitro studies, VDR knockout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…In animal experiments, vitamin D was found to be a potent endocrine suppressor of renin biosynthesis: VDR -/mice had elevated production of renin and angiotensin II, causing hypertension, cardiac hypertrophy, and increased water intake [24,25]. Chandel et al [26] analyzed how VDR modulates the RAAS activity finding that vitamin D receptor deficit induces its activation through SIRT1/PPAR-c/VDR signaling in podocytes. Zittermann et al [27] evaluated the effect of three years of vitamin D supplementation (4000 IU daily) on parameters of the RAAS (renin and aldosterone) in 165 patients with advanced heart failure, with a not significant change in RAAS parameters; nevertheless, the study showed an increase in serum renin concentrations in the subgroup with low baseline 25OHD levels.…”
Section: Vitamin D and The Cardiovascular Tissue: Pathophysiological mentioning
confidence: 99%
“…In animal experiments, vitamin D was found to be a potent endocrine suppressor of renin biosynthesis: VDR -/mice had elevated production of renin and angiotensin II, causing hypertension, cardiac hypertrophy, and increased water intake [24,25]. Chandel et al [26] analyzed how VDR modulates the RAAS activity finding that vitamin D receptor deficit induces its activation through SIRT1/PPAR-c/VDR signaling in podocytes. Zittermann et al [27] evaluated the effect of three years of vitamin D supplementation (4000 IU daily) on parameters of the RAAS (renin and aldosterone) in 165 patients with advanced heart failure, with a not significant change in RAAS parameters; nevertheless, the study showed an increase in serum renin concentrations in the subgroup with low baseline 25OHD levels.…”
Section: Vitamin D and The Cardiovascular Tissue: Pathophysiological mentioning
confidence: 99%
“…Vitamin D deficiency aggravates tenofovir-induced nephrotoxicity because of enhanced activation of the RAS in the kidney [ 91 ]. In vitro studies confirm that VDR knockout podocytes display upregulation of angiotensinogen [ 92 ]. In rats with diabetes, calcitriol treatment attenuates renal pathological abnormalities by blocking the activation of the local RAS [ 93 - 95 ].…”
Section: Renoprotective Mechanisms Of Vdrmentioning
confidence: 99%
“…al . recently demonstrated that Pparg expression is downregulated in podocytes from vitamin D receptor ( Vdr ) null mice via a mechanism involving suppression of sirtuin 1 ( Sirt1 ) [ 51 ]. While we did not observe downregulation of Sirt1 in our model, Vdr was significantly suppressed in CoRL at day 5 post-FSGS induction (FDR < 0.01).…”
Section: Discussionmentioning
confidence: 99%